The Development of Interactive Learning Multimedia Based on The Website for Mathematics’ Subject in Junior High School - Irmawan Irmawan; Aloysius Mering; Indri Astuti (JETL (Journal of Education, Teaching and Learning), 2022)
This research aims to develop interactive learning media based on the website for mathematics subjects in junior high school. The research and development (R&D) method was applied to this research to achieve that goal and the model used is ADDIE. ADDIE model consists of five phases: (1) Analyze, (2) Design, (3) Develop, (4) Implement, and (5) Evaluate. The research was conducted in grade 8 students of SMPS Kristen Makedonia Ngabang with 27 participants and six people for a validity test based on media design experts, media experts, and mathematics content experts. Questionnaire instruments and attitude scales were used to analyze the quantitative and qualitative data. Overall, according to the data analysis (with the frequency range of 1 to 5), it is found that the media design has met very valid criteria with an average value of 4,76. Nonetheless, the analysis result of empirical assessment for individual, small group, and field try procedures for 27 students in SMPS Kristen Makedonia Ngabang grade 8 expressed that the students are very happy to use interactive learning multimedia based on the website with an average value of 6,27 with the frequency range of 1 to 7. Furthermore, according to the result of the effectiveness attitude questionnaire towards media and the pre-treatment and post-treatment analysis that involved 30 students, there was a significant difference as , (). Therefore, the interactive learning multimedia based on the website for mathematics subjects in junior high school can be implemented for mathematics-related topics in junior high school.